EU needs more from bioeconomy - Kohl, Johanna; Lehto, Jani; Kaukovirta, Anu; Asikainen, Antti; Kurttila, Mikko; Buchert, Johanna (Natural Resources Institute Finland (Luke), 2024)
We are facing a polycrisis. The EU’s competitiveness has been severely weakened by geopolitical tensions, the COVID pandemic and the faster economic development of our competitors. The EU’s heavy dependence on imported production inputs and feedstock also poses a growing risk to our security of supply. At the same time, globally we need long-term solutions to biodiversity loss and adaptation to climate change. Sustainable bioeconomy can provide solutions to these challenges. Europe needs bioeconomy to transition from niche to norm.
Keywords: bioeconomy; polycrisis